Medical students' exposure to, knowledge and perceptions of telehealth technology: is our future workforce ready to embrace telehealth service delivery? (Health Education in Practice: Journal of Research for Professional Learning, 2018)
Background: Having a workforce ready to embrace telehealth is key to improving healthcare access and equity in rural Australia. Known barriers to uptake amongst health professionals include: liability/law issues; traditional attitudes; business models; time constraints; and lack of workforce support, incentives, billing, funding, information technology (IT) skills, and patient rapport. Whether medical students share the same perspectives is currently unclear. This study sought to explore medical students’ knowledge of, exposure to and attitudes towards telehealth.Methods: Focus groups were conducted upon completion of a 12-month rural placement. Questions focused on students’ exposure to and experiences with telehealth, their perspectives on those experiences, their desire to learn more about telehealth, and their perspectives on who should drive the implementation of telehealth services. Thematic analysis was conducted to identify key themes.Results: Exposure to telehealth consults varied and appeared ad hoc. Overall interest in telehealth appeared to be low, but the students recognised its value in specific circumstances, such as for scripts, complicated/rare cases and to reduce social isolation for patients and doctors. Students identified the following as key barriers to telehealth use: legal/liability issues, technology, organisational issues, patient rapport, potential lower quality of care, lack of confidence in clinical ability, and a preference for ‘face-to-face’ medicine. Overall, students felt that rural, rather than urban-based, clinicians need to drive the telehealth agenda and further telehealth skills training and guidelines are required. Some students felt that some urban doctors used telehealth to expand their own patient base.Conclusion: Medical students’ ‘real life’ experience influences their current knowledge and perceptions of telehealth, which in turn has implications for the future of telehealth work and education of the workforce. Enhancing telehealth education and training during medical school training through increased exposure, experience and capability building will make medical students more workforce ready, so they are able to develop and work in new models of telehealth care. Article submitted: 10/10/2018Article accepted: 18/11/2018Publish date: 17/12/2018